Psychological well-being of the parents and child development, behavior, and quality of life in very low birth weight infants - Huhtala, Mira (Annales Universitatis Turkuensis D 1197, 2015)
The parents of premature infants, especially the mothers, are at increased risk for distress. Infants born prematurely are at risk for developmental problems. The aim of this study was to investigate whether the psychological well-being of both parents is associated with child development in very low birth weight (VLBW, ≤1500g) children. The burden of prematurity-related morbidity to the children and to the family was also assessed. A cohort of 201 VLBW infants born during 2001–2006 in the Turku University Hospital, Finland, and their parents were studied (I–IV). One study included a control group (n=166) of full-term infants (IV). The psychological well-being of the parents was evaluated by assessments of depressive symptoms, parenting stress, the sense of coherence and general family functioning. Cognitive, behavioral, and socio-emotional development, and the health-related quality of life (HRQoL) of the children were determined when the children were 2 to 8 years old. The psychological well-being of the parents was associated with the cognitive, behavioral and social development of the VLBW children. The VLBW infants with prematurity-related morbidities had a poorer HRQoL and the general functioning of the family was inferior compared to the control children and their families. 64.5% of the VLBW children survived without morbidities. Most of the VLBW children did not have significant behavior problems (93%), had normal social skills (63%), had no emotional problems (64%), and had no problems in executive functioning (62%). Only 3% of the surviving VLBW infants had significant cognitive delay. In conclusion, the depressive symptoms and stress of the parents can be risk factors for disadvantageous child development, while a strong sense of coherence can be protective. Parents of the premature children with developmental delays might also experience more depressive symptoms and stress than other parents. Prematurity-related morbidities were a burden to the VLBW child as well as to the family.

Vanhempien psyykkinen hyvinvointi ja hyvin pienipainoisena syntyneiden lasten kehitys, käyttäytyminen ja elämänlaatu Keskosten vanhemmilla, varsinkin äideillä, on riski ahdistua ja masentua. Keskosten elämää voivat varjostaa kehitykselliset ongelmat. Tämän tutkimuksen tarkoituksena oli selvittää molempien vanhempien psyykkisen hyvinvoinnin yhteyttä pienipainoisena syntyneen keskoslapsen (syntymäpaino ≤1500 g) kehitykseen. Lisäksi tutkittiin keskosilla yliedustetuiksi todettujen sairauksien vaikutusta lapsen elämänlaatuun ja perheen yleiseen toimivuuteen.Tutkimukseen otettiin 201 vuosina 2001–2006 Turun yliopistollisessa keskussairaalassa hyvin pienipainoisena syntynyttä keskosta vanhempineen (I–IV). Yhdessä tutkimuksessa (IV) oli mukana verrokkiryhmä (n=166). Vanhempien psyykkistä hyvinvointia arvioitiin heidän kokemiensa masennusoireiden, vanhemmuuden stressin ja elämänhallinnan tunteen kautta. Myös perheen yleinen toimivuus kartoitettiin. Keskosilta arvioitiin kognitiivinen kehitys, käyttäytymisvaikeudet, sosio-emotionaalinen kehitys ja terveyteen liittyvä elämänlaatu eri ikäpisteissä 2–8 vuotiaina. Vanhempien psyykkinen hyvinvointi oli yhteydessä keskoslasten kehitykseen. Niillä keskosilla, joilla oli pitkäaikaissairauksia, oli myös huonompi terveyteen liittyvä elämänlaatu ja heidän perheissään oli huonompi toimintakyky. Suurin osa keskosista selviytyi ilman keskosuuteen liittyviä pitkäaikaissairauksia (64.5%), ilman merkittäviä käytösongelmia (93%), ilman tunne-elämän ongelmia (64%) ja ilman toiminnanohjauksen ongelmia (62%). 63%:lla oli normaalit sosiaaliset taidot ja vain 3%:lla oli merkittävä kognitiivisen kehityksen viive. Yhteenvetona todettiin, että keskoslasten vanhempien kokemat masennusoireet ja vanhemmuuden stressi voivat olla uhka keskoslasten normaalille kehitykselle, kun taas vanhempien hyvä elämänhallinnan tunne voi olla suojaava tekijä. On myös mahdollista, että kehityksessään viiveisten lasten vanhemmat voivat kokea muita vanhempia enemmän masennusta ja stressiä. Keskoslasten pitkäaikaissairaudet ovat taakka lapselle itselleen mutta myös koko perheelle.